Ireland 1798-1998 War, Peace and Beyond - Jackson, Alvin (Wiley, 2025)
The new edition of Alvin Jackson’s highly influential survey of 200 years of Irish history In Ireland, 1798-1998: War, Peace, and Beyond, award-winning historian Alvin Jackson provides a well-balanced and authoritative account of modern Irish political history. Drawing on original research and extensive readings in current scholarship, the author surveys Irish political parties, leaders, and movements with a special emphasis on the tension between Irish nationalism and unionism. Opening with a wide-ranging introduction to Irish history, the text describes the varieties and interconnections of the Irish political experience through a sustained and coherent historical narrative, beginning with the creation of militant republicanism and militant loyalism in the 1790s. Reader-friendly chapters interweave social, economic, and cultural material while offering fresh analyses of familiar historical issues and personalities. This third edition contains expanded coverage of the most recent political developments in Ireland, both North and South. A new epilogue examines the impacts of the Good Friday Agreement, the global banking crisis, Brexit, and COVID-19 on Irish politics and institutions. The most up-to-date interpretation of modern Irish political history available in a single volume, Ireland, 1798-1998: War, Peace, and Beyond, Third Edition, is a must-read for undergraduate and graduate students working on Irish and British political history, as well as general readers with an interest in the subject